The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12575-019-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Differential Gene Expression to Discover Ionic and Osmotic-Associated Transcripts in the Halophyte Grass Aeluropus littoralis

Abstract: Background Salinity as a most significant environmental challenges affects the growth and productivity of plants worldwide. In this study, the ionic and iso-osmotic effects of salt stress were investigated in Aeluropus littoralis L., a halophyte grass species from Poaceae family, by cDNA-amplified fragment length polymorphism (cDNA-AFLP) technique. To dissect the two different effects (ionic and osmotic) exerted by salt stress, various ionic agents including 200 and 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
3
12
0
1
Order By: Relevance
“…Hence, it can be stated that 200 mM NaCl is not detected as stress condition, but 400 mM NaCl induces the most stress-related terms in the A. littoralis. Our results support previous findings that 200 mM NaCl enhances the biomass of A. littoralis in liquid MS culture medium 29 and also increases the root length in comparison with control plants 30 .…”
Section: Discussionsupporting
confidence: 92%
“…Hence, it can be stated that 200 mM NaCl is not detected as stress condition, but 400 mM NaCl induces the most stress-related terms in the A. littoralis. Our results support previous findings that 200 mM NaCl enhances the biomass of A. littoralis in liquid MS culture medium 29 and also increases the root length in comparison with control plants 30 .…”
Section: Discussionsupporting
confidence: 92%
“…compared to a control [43]. The results also showed that potassium chloride was more toxic than sodium chloride, and the K + ion affected plant growth more than the Na + ion [43]. Another study of five selected landscape ornamental species demonstrated that plant growth decreased when irrigated with increasing NaCl + CaCl 2 concentrations [44].…”
Section: Introductionmentioning
confidence: 95%
“…In the case of Salicornia europaea L., good germination of large seeds occurred under NaCl between 0.5 and 2%, under Na 2 SO 4 and 2NaCl + KCl + CaCl 2 between 0.5 and 3%, and under 2Na 2 SO 4 + K 2 SO 4 + MgSO 4 between 0.5 and 5% [42]. Fatemi et al [43] indicated that salinity stresses induced by 200 mM and 400 mM KCl and polyethylene glycol (PEG, the nonpenetrant osmotic agent) significantly reduced the fresh weight of the halophyte grass Aeluropus littoralis (Gouan) Parl. compared to a control [43].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Genome-wide transcript pro ling techniques play an important role in large-scale screening and characterization of the genes involved in various biological processes. Since the advent of the cDNA-AFLP transcript-pro ling technique in 1996 [22], owing to its advantages of good repeatability, high sensitivity and high throughput, this technique has been successfully applied to the eld of plant biology, such as abiotic stress response [23], plant-microorganism interaction [24], hormone signal [25] and development [26].…”
Section: Introductionmentioning
confidence: 99%